2021
DOI: 10.1093/ptj/pzab173
|View full text |Cite
|
Sign up to set email alerts
|

Functional Reach Test, Single-Leg Stance Test, and Tinetti Performance-Oriented Mobility Assessment for the Prediction of Falls in Older Adults: A Systematic Review

Abstract: OBJECTIVE To systematically review the existing literature on the falls-related diagnostic test properties of the Functional Reach Test (FRT), single-leg stance test (SLST), and Tinetti Performance-Oriented Mobility Assessment (POMA) in older adults across settings and patient populations. METHODS Databases PubMed, EMBASE, and CINAHL were searched (inception–July 2020). Inclusion criteria were an age of 60 years or more for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 65 publications
0
32
0
2
Order By: Relevance
“…In the present review, the four most common tests used to assess physical performance were SPPB ( 39 ), PPT ( 40 ), SLS ( 41 ) and TUG ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…In the present review, the four most common tests used to assess physical performance were SPPB ( 39 ), PPT ( 40 ), SLS ( 41 ) and TUG ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…Single-leg stance is particularly important in falls prevention; evidence suggests that 40% of gait cycle is comprised of the single-leg stance [27]. Additionally, single-leg stance has been able to predict falls [28,29] and is a valid measure of discerning older adults who fall and who do not fall among community-dwelling older adults [30]. Rissel and colleagues (2013) found that single-leg stance balance improved for older adult participants in a cycling intervention [13].…”
Section: Discussionmentioning
confidence: 99%
“…The sway during the quiet balance test with force plates 21 and the functional reach test (FRT) 22 were adopted as balance tests. Three floor conditions were used for balance evaluation: MM-flooring, shock-absorbing mat and rigid floor.…”
Section: Methodsmentioning
confidence: 99%